2018
DOI: 10.1038/s41598-018-29377-8
|View full text |Cite|
|
Sign up to set email alerts
|

Social context influences the expression of DNA methyltransferase genes in the honeybee

Abstract: DNA methylation is a reversible epigenetic modification that alters gene expression without altering the nucleotide sequence. Epigenetic modifications have been suggested as crucial mediators between social interactions and gene expression in mammals. However, little is known about the role of DNA methylation in the life cycle of social invertebrates. Recently, honeybees have become an attractive model to study epigenetic processes in social contexts. Although DNA methyltransferase (DNMT) enzymes responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
(58 reference statements)
1
17
0
Order By: Relevance
“…The expression of DNMTs changes with chronological age and is sensitive to diverse social stimuli that affect ageing in the honey bee (Holman et al . 2016; Cardoso-Junior et al . 2018) and ants (Holman et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of DNMTs changes with chronological age and is sensitive to diverse social stimuli that affect ageing in the honey bee (Holman et al . 2016; Cardoso-Junior et al . 2018) and ants (Holman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic mechanisms are a likely mediator between the social environment and global gene expression responses (Cardoso-Junior et al . 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agonistic social encounters, in particular, are a source of physiological stress (Masis‐Calvo et al, ). In this regard, it has been shown that agonistic interactions affect DNA methylation patterns (i.e., Cardoso‐Júnior, Eyer, Dainat, Hartfelder, & Dietemann, ; Turecki & Meaney, ). Epigenetic changes lead phenotypic plasticity to adjust physiological responses to novel conditions (Duncan, Gluckman, & Dearden, ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation patterns (i.e., Cardoso-Júnior, Eyer, Dainat, Hartfelder, & Dietemann, 2018;Turecki & Meaney, 2016).…”
mentioning
confidence: 99%